MOTIVASI DAN HASIL BELAJAR SISWA KELAS X PADA MATERI EKOSISTEM MELALUI PEMBELAJARAN BERBASIS MASALAH (PBL) - Mustika Piliang, Fenny; Rosenta Purba, Ika; Sinaga, Fiana (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2024)
This research aims to determine the effect of the project based learning model on student motivation and learning outcomes. in a pretest-posttest control group design. The research population was 75 students consisting of 2 classes at SMA Muhammadiah – 7 Serbelawan for the 2023/2024 academic year. The research sample was 75 students consisting of 2 classes, Student motivation is measured using a questionnaire while learning outcomes are measured using a multiple choice test. Next, the data obtained were analyzed using quantitative descriptive analysis by carrying out analytical prerequisite tests and hypothesis testing with a significance level of α = 0.05. The results of this research show that there is a significant influence in using the project based learning model on student learning motivation with a probability value of 0,05 (0,000 < 0,05) and tcount (0, 511) > ttable(1,666) and it can be concluded that Ha is accepted and H0 is rejected, which means there is a significant influence using a project based learning model on student learning outcomes with a probability value of 0,05 (0,000 < 0,05) and tcount 9,906 > ttable 3,122